Cerebellar tDCS Does Not Enhance Performance in an Implicit Categorization Learning Task - Verhage, Marie C.; Avila, Eric O.; Frens, Maarten A.; Donchin, Opher; van der Geest, Jos N. (Frontiers in Psychology, 2017)
Background: tDCS (transcranial Direct Current Stimulation) is a form of non-invasive electrical stimulation that changes neuronal excitability in a polarity and site-specific manner. In cognitive tasks related to prefrontal and cerebellar learning, cortical tDCS arguably facilitates learning, but the few studies investigating cerebellar tDCS, however, are inconsistent. Objective: We investigate the effect of cerebellar tDCS on performance of an implicit categorization learning task. Methods: 40 participants performed a computerized version of an implicit categorization learning task where squares had to be sorted into two categories, according to an unknown but fixed rule that integrated both the size and luminance of the square. Participants did one round of categorization to familiarize themselves with the task and to provide a baseline of performance. After that, 20 participants received anodal tDCS (20 min. 1.5mA) over the right cerebellum, and 19 participants received sham stimulation and simultaneously started a second session of the categorization task using a new rule. Results: As expected, subjects performed better in the second session than in the first, baseline session, showing increased accuracy scores, and reduced reaction times. Over trials, participants learned the categorization rule, improving their accuracy and reaction times. However, we observed no effect of anodal tDCS stimulation on overall performance or on learning, compared to sham stimulation. Conclusions: These results suggest that cerebellar tDCS does not modulate performance and learning on an implicit categorization task.